Generation of Tetracycline and Rifamycin Resistant Chlamydia Suis Recombinants - Marti, Hanna; Bommana, Sankhya; Read, Timothy D.; Pesch, Theresa; Prähauser, Barbara; Dean, Deborah; Borel, Nicole (Frontiers in Microbiology, 2021)
The Chlamydiaceae are a family of obligate intracellular, gram-negative bacteria known to readily exchange DNA by homologous recombination upon co-culture in vitro, allowing the transfer of antibiotic resistance residing on the chlamydial chromosome. Among all the obligate intracellular bacteria, only Chlamydia (C.) suis naturally integrated a tetracycline resistance gene into its chromosome. Therefore, in order to further investigate the readiness of Chlamydia to exchange DNA and especially antibiotic resistance, C. suis is an excellent model to advance existing co-culture protocols allowing the identification of factors crucial to promote homologous recombination in vitro. With this strategy, we co-cultured tetracycline-resistant with rifamycin group-resistant C. suis, which resulted in an allover recombination efficiency of 28%. We found that simultaneous selection is crucial to increase the number of recombinants, that sub-inhibitory concentrations of tetracycline inhibit rather than promote the selection of double-resistant recombinants, and identified a recombination-deficient C. suis field isolate, strain SWA-110 (1-28b). While tetracycline resistance was detected in field isolates, rifampicin/rifamycin resistance (RifR) had to be induced in vitro. Here, we describe the protocol with which RifR C. suis strains were generated and confirmed. Subsequent whole-genome sequencing then revealed that G530E and D461A mutations in rpoB, a gene encoding for the -subunit of the bacterial RNA polymerase (RNAP), was likely responsible for rifampicin and rifamycin resistance, respectively. Finally, whole-genome sequencing of recombinants obtained by co-culture revealed that recombinants picked from the same plate may be sibling clones and confirmed C. suis genome plasticity by revealing variable, apparently non-specific areas of recombination.